Kizomba Dance: From Market Success to Controversial National Brand - (:unkn) unknown (My University, 2019)
This paper aims to analyze how the global contra-flow of a dance style — kizomba — generated an impact on the symbolic representation of a nation — Angola — nd the controversies this national branding involves. The kizomba couple dance style became popular in some Portuguese-speaking African cities and nightclubs in Lisbon in the 1980s. In the mid-1990s, the style underwent commodification in Portugal. In less than ten years, it went onto become a global dance industry in which teachers compete to attract students and correspondingly triggering heated debates on the Angolan-ness, Cape-Verdean-ness, African-ness or the global character of kizomba to legitimize their own practices. In this context, the Angolan state has also capitalized on kizomba’s global success to claim the music and the dance as national symbols. Our conclusion points to how global industries have gained greater influence over the definition of national symbols in late modernity, a process to which former colonies would seem more vulnerable.
Keywords: African Research